Initiating the Bank's Peri-Urban/Rural and Renewable Energy Activities in Nigeria - World Bank (Washington, DC, 2014)
The workshop entitled, Initiating the Bank's Peri Urban / Rural and Renewable Energy Activities in Nigeria was divided in two parts. Part 1, Energizing rural energy transformation by : scaling up electricity access and renewable energy market development; and part 2, Creating demand and removing barriers to renewable energy market development. The workshop organizers placed great emphasis on promoting participation and dialog across Nigeria's energy sector. Delegates were major stakeholders in the rural electrification arena. This document lists the proceedings, and includes the presentations by participants of the overall workshop. The workshop concluded by identifying the following areas for action : accelerate the process of formulating Nigeria's overall vision for scaling up electricity access from renewable energy sources in underserved areas in a rapid and sustainable manner; identify key principles for framing the policy platform and institutional framework required for mounting a large-scale clean energy program; formulate a strategy for developing renewable and clean energy resources in a cost effective manner, while supporting the twin objectives of poverty reduction and improved environmental conditions; and initiate the process of formulating Nigeria's strategy for rural energy provision for rural transformation, taking into account lessons learned and best practices from other key countries.